The United States and the Arab Spring : Threats and Opportunities in a Revolutionary Era. - Haas, Mark L. (Westview Press Spotlight., 2013)
In this Westview Press Spotlight, Mark L. Haas explores the major political consequences of the Arab Spring protests in North Africa and the Middle East as well as how and why U.S. leaders responded to these developments.